Electronic and structural study of hexagonal TiC nanowires: ab initio study - Puspa Raj Adhikari (Bibechana, 2018)
Nanowire are the one-dimensional nanostructure with the diameter order of one to few hundred nanometre. These structure shows unique properties other than their bulk structures. In this article, a qualitative first principle discussion of TiC nanowire is reported, indicating the impact of DFT based GGA relativistic corrections on its electronic properties. Here, we analyse   the Titanium Carbide (TiC) nanowire of hexagonal structure periodic in Z-direction with the density functional theory (DFT). The GGA with RBBE Correlation analysis of this material shows the metallic characteristics in its bulk but the electronic density of  state shows that the hybridization state are different from their bulk when the material is analysed in nanostructure form. Three structures of hexagonal TiC nanowire directed in (1,1,1) plane were analysed to explore diameter (4-18) Å dependent comparative study of electronic, stabilizing and optical property which shows unique different result counterparts to its bulk. Hexagonal TiC nanowire were found to be semiconducting with narrow band gap (0.21-0.34) eV in small diameter while metallic in higher diameter. They are comparable stables as their bulk for higher structure. Similarly, for the same investigation, the structures are cross checked by surface atom passivation to verify the reliability of the result that we found. BIBECHANA 16 (2019) 7-14